Consumption of green tea - potential health benefits - Żuchnik, Olga; Szydłowska, Justyna; Gładysz, Konrad; Kwiatkowski, Piotr; Szydłowski, Marcin; Kłos, Aleksander; Kuczyńska, Beata; Gieroba, Krzysztof; Czelej, Magda; Król, Olgierd (Journal of Education, Health and Sport, 2022)
Introduction: The health-promoting effects of green tea have been known since ancient times. Nowadays it is one of the most consumed beverages in the world. The main bioactive components of green tea are the catechins: epicatechin, epigallocatechin, epicatechin gallate and epigallocatechin gallate. They have a number of health-promoting properties. Aim of the study: The aim of this study was to compile the health benefits of drinking green tea. Methods and materials: A review of the literature available in the PubMed database and Google Scholar, the following keywords were used: "green tea", “catechins", "health benefits". Results: Consumption of green tea carries a number of health benefits, such as anti-inflammatory, antioxidant and neuroprotective effects. Due to its potential for preventing many diseases and supporting cognitive function, regular consumption of green tea may have a positive effect on both physical and mental health. Conclusion: Studies on the effects of green tea on the human body have shown that it can be an important dietary factor in preventing and supporting the treatment of various diseases, such as inflammation, diabetes, obesity, neurological diseases and neurodegenerative disorders. By affecting crucial cellular processes, it prevents the formation, growth and progression of cancer. In addition, the catechins in green tea also play an important role in preventing and treating infections. Daily consumption of adequate amounts of green tea inhibits brain aging by activating nerve cells and reducing stress. When consumed regularly, green tea can support the body’s efforts to maintain health and prevent disease.